2000
DOI: 10.1073/pnas.260502697
|View full text |Cite
|
Sign up to set email alerts
|

TheSUR2gene ofArabidopsis thalianaencodes the cytochrome P450 CYP83B1, a modulator of auxin homeostasis

Abstract: Genetic screens have been performed to identify mutants with altered auxin homeostasis in Arabidopsis. A tagged allele of the auxin-overproducing mutant sur2 was identified within a transposon mutagenized population. The SUR2 gene was cloned and shown to encode the CYP83B1 protein, which belongs to the large family of the P450-dependent monooxygenases. SUR2 expression is up-regulated in sur1 mutants and induced by exogenous auxin in the wild type. Analysis of indole-3-acetic acid (IAA) synthesis and metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
231
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(249 citation statements)
references
References 35 publications
16
231
1
1
Order By: Relevance
“…These results are in agreement with other reports in which the modiWcation of endogenous free IAA level caused similar modiWcation of the auxin catabolites and conjugates (e.g. Barlier et al 2000). A signiWcant reduction of the auxin level due to the ectopic overexpression of APRX was observed in OE-APRX roots.…”
Section: Aprx Is Involved In Auxin Catabolismsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with other reports in which the modiWcation of endogenous free IAA level caused similar modiWcation of the auxin catabolites and conjugates (e.g. Barlier et al 2000). A signiWcant reduction of the auxin level due to the ectopic overexpression of APRX was observed in OE-APRX roots.…”
Section: Aprx Is Involved In Auxin Catabolismsupporting
confidence: 93%
“…The balance between auxin biosynthesis and metabolism, including conjugation, deconjugation, and catabolism, determines the level of the active hormone (Bartel 1997). In A. thaliana several genes involved in auxin homeostasis are known to contain auxin response elements in their promoters (Barlier et al 2000). Furthermore recent studies have revealed that speciWc auxin-mediated responses are controlled via a negative (auto)feedback loop (Tatematsu et al 2004).…”
Section: Aprx Is Involved In Auxin Catabolismmentioning
confidence: 99%
“…This strongly suggested that rnt1-1 is an allele of sur2 , a mutant known to accumulate elevated levels of free IAA . Recently, sur2 was indeed demonstrated to be a CYP83B1 mutant (Barlier et al, 2000). As described for sur2 seedlings, rnt1-1 seedlings are characterized by increased hypocotyl length, epinastic cotyledons, exfoliation of the hypocotyl, adventitious root formation from the hypocotyl, enhanced secondary root and root hair formation, and eventually callus formation and increasing disintegration of the seedling (Table 1 and Figures 1 and 2).…”
mentioning
confidence: 79%
“…In addition, we have shown that CYP83B1 catalyzes the first committed step in indole glucosinolate biosynthesis by metabolizing indole-3-acetaldoxime to its corresponding aci-nitro compound. The recently reported identity of sur2 also as CYP83B1 (Barlier et al, 2000) explains the strong auxin phenotype of the rnt1-1 mutant, which is a knockout for CYP83B1. Increased free auxin levels were previously measured in the sur2 mutant ).…”
mentioning
confidence: 93%
“…Mutants overproducing auxin in Arabidopsis, like sur1 and sur2 (Boerjan et al, 1995;Delarue et al, 1998) or yucca (Zhao et al, 2001) produce adventitious roots on hypocotyls of light grown seedlings. SUR1 and SUR2 genes encode a C-S-lyase protein and the cytochrome P450 Cyp83B1, both involved in the indole glucosinolate pathway (Bak et al, 2001;Barlier et al, 2000;Mikkelsen et al, 2004). YUCCA1 gene encodes a flavin monooxygenase suitable for converting tryptamine in N-hydroxyl tryptamine in vitro (Zhao et al, 2001(Zhao et al, , 2002) and belongs to a family of YUCflavin mono-oxigenases from which 4 have a role in auxin biosynthesis (Cheng et al, 2006).…”
Section: Genes Asociated With the Adventitious Root Formationmentioning
confidence: 99%